2002
DOI: 10.1074/jbc.m111795200
|View full text |Cite
|
Sign up to set email alerts
|

FOR, a Novel Orphan Nuclear Receptor Related to Farnesoid X Receptor

Abstract: We have identified and characterized a new amphibian orphan member of the nuclear receptor superfamily and termed it FOR1 (farnesoid X receptor (FXR)-like Orphan Receptor) because it shares the highest amino acid identity with the mammalian FXR. We also identi- The nuclear receptor superfamily comprises a large group of structurally related ligand-dependent transcription factors regulated by a variety of steroid and non-steroid hormones. It also includes a large number of related proteins that do not have know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…3B) and severe reduction in the formation of anterior endodermal tissue, such as liver, as judged by LFABP (Fig. 3F) and For1 (Seo et al, 2002) (data not shown). The apparent synergism between SOX17βEnR and GATA4 in promoting cardiac tissue differentiation suggests that GATA4 may induce endoderm at B. V. Latinkić, S. Kotecha and T. J. Mohun the expense of cardiac tissue.…”
Section: Sox17-dependent Endoderm Antagonises Cardiogenesis By Gata4mentioning
confidence: 82%
See 1 more Smart Citation
“…3B) and severe reduction in the formation of anterior endodermal tissue, such as liver, as judged by LFABP (Fig. 3F) and For1 (Seo et al, 2002) (data not shown). The apparent synergism between SOX17βEnR and GATA4 in promoting cardiac tissue differentiation suggests that GATA4 may induce endoderm at B. V. Latinkić, S. Kotecha and T. J. Mohun the expense of cardiac tissue.…”
Section: Sox17-dependent Endoderm Antagonises Cardiogenesis By Gata4mentioning
confidence: 82%
“…15-20 animal caps were used per sample. The templates for riboprobes were: MHCα (Logan and Mohun, 1993), MLC2 (Chambers et al, 1994), cTnI , IFABP (Shi and Hayes, 1994), Sox17α (Hudson et al, 1997), MyoD (Hopwood et al, 1989), MLC1 (Theze et al, 1995), Eomesodermin , globin (Patient et al, 1982), Nkx2.3 (Evans et al, 1995), Nkx2.5 , For1 (Seo et al, 2002), EF1α, amylase and insulin (Horb and Slack, 2002). For the LFABP probe, we used the 5′ end of cDNA [derived by 5′ RACE using partial cDNA information; see Henry and Melton (Henry and Melton, 1998)].…”
Section: Rna and Dna Injectionsmentioning
confidence: 99%
“…The high degree of conservation of the vertebrate LXRs contrasts with divergence of FXRs across species. For example, the Xenopus laevis FXR has markedly different pharmacology from mammalian FXRs and also has a novel insert in the LBD not found in human or rodent FXRs [37].…”
Section: Discussionmentioning
confidence: 99%
“…Human FXR may have retained affinity for these precursors during evolution. A recent study has shown that FXR-like orphan receptors (FORs), identified in Xenopus laevis liver and kidney, are not activated by bile acids but are activated by bullfrog gallbladder bile extracts (52), which contain bile alcohols (53).…”
Section: Discussionmentioning
confidence: 99%